2021
DOI: 10.3390/cancers13184653
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Lifestyle-Related Prognostic Indicators among Esophageal Adenocarcinoma Patients Receiving Treatment at a Comprehensive Cancer Center

Abstract: Purpose: The incidence of esophageal adenocarcinoma (EAC) has risen substantially in recent decades, while the average 5-year survival remains only ~20%. Disease stage and treatment are the strongest prognostic factors. The role of lifestyle factors in relation to survival remains uncertain, with a handful of studies to date investigating associations with obesity, smoking, physical activity, diet, or medications. Methods: This study included patients diagnosed with primary adenocarcinoma of the esophagus, gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Other studies showed improved outcomes in statin users when used after diagnosis [158,159]. Our group was able to show an overall and cancer-specific survival benefit of statins when they were used prior to esophageal adenocarcinoma diagnosis [157].…”
Section: Statinssupporting
confidence: 53%
See 2 more Smart Citations
“…Other studies showed improved outcomes in statin users when used after diagnosis [158,159]. Our group was able to show an overall and cancer-specific survival benefit of statins when they were used prior to esophageal adenocarcinoma diagnosis [157].…”
Section: Statinssupporting
confidence: 53%
“…Statins have improved overall survival in stage four esophageal cancer patients [157]. Other studies showed improved outcomes in statin users when used after diagnosis [158,159].…”
Section: Statinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Physical activity evokes growing interest in cancer patient rehabilitation [ 1 ]. An increasing number of studies have shown that low to moderate-intensity exercises could help cancer patients to recover, deal with treatment, and also have an impact on extending survival time [ 2 , 3 , 4 , 5 ]. It is worth mentioning that physical activity leads to improved physiological and psychological functioning in oncological patients (a rehabilitation of patients with advanced cancer).…”
Section: Introductionmentioning
confidence: 99%
“…[17] To date, several studies have explored the association between statin use and survival in esophageal cancer. [18][19][20][21][22][23][24] However, their results are inconsistent and conflicting.…”
Section: Introductionmentioning
confidence: 99%